Anais Do II Inovagri International Meeting - 2014 2014
DOI: 10.12702/ii.inovagri.2014-a280
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiração de Referência para Dimensionamento de Sistemas de Irrigação em Petrolina, PE

Abstract: A evapotranspiração é uma variável fundamental para estimar a exigência hídrica das culturas, e também fornece subsídio para o dimensionamento de sistemas de bombeamento, adução e distribuição de água na irrigação. A caracterização da distribuição de frequência da evapotranspiração de referência (ETo), estimada pelo método do tanque classe "A" em Petrolina-PE, foi realizada com base em série histórica de dados de 1963 a 2010, os quais foram agrupados em períodos de 5, 10, 15 e 30 dias. As distribuições gama e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…Assis et al (2014) verified that the reference evapotranspiration data from Mossoró-RN can be adjusted to the normal probability distribution. On the other hand, Silva et al (2015) observed that the normal and gamma distributions were able to represent the Petrolina-PE reference evapotranspiration data, for the cumulative periods of 10, 15 and 30 days. Silva et al (2014) verified the presence of theoretical distribution of probability by means of the chi-square and the Kolmogorov-Smirnov test (at 5% of significance) in Crateús, Quixeramobim and Tauá in the state of Ceará.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Assis et al (2014) verified that the reference evapotranspiration data from Mossoró-RN can be adjusted to the normal probability distribution. On the other hand, Silva et al (2015) observed that the normal and gamma distributions were able to represent the Petrolina-PE reference evapotranspiration data, for the cumulative periods of 10, 15 and 30 days. Silva et al (2014) verified the presence of theoretical distribution of probability by means of the chi-square and the Kolmogorov-Smirnov test (at 5% of significance) in Crateús, Quixeramobim and Tauá in the state of Ceará.…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, Silva et al (2015) observed that the normal and gamma distributions were able to represent the Petrolina-PE reference evapotranspiration data, for the cumulative periods of 10, 15 and 30 days. Silva et al (2014) verified the presence of theoretical distribution of probability by means of the chi-square and the Kolmogorov-Smirnov test (at 5% of significance) in Crateús, Quixeramobim and Tauá in the state of Ceará. Then, normal, log-normal and range distributions were adjusted to monthly reference evapotranspiration (Eto) data in all months of the year.…”
Section: Introductionmentioning
confidence: 90%
“…Para condições climáticas de Mossoró, RN, o modelo de distribuição Log-Normal pode ser usado para estimar a probabilidade de ocorrência de ET o média para períodos mensais, segundo o teste KS (SANTOS et al, 2011;PEIXOTO et al, 2011b). Nas condições climáticas de Petrolina, PE, a distribuição Gama mostrou-se apta estatisticamente para representar os dados de ET o em escala quinzenal mediante a comprovação pelo teste KS a 5% (SILVA et al, 2014a) e em escala pentadial a 20% de significância (SOUZA et al, 2014).…”
Section: -574punclassified
“…Several works of adjustment of theoretical distributions or probability density involving climate variables, such as evapotranspiration, have been developed emphasizing the benefits of reducing probable climate risks in activity planning (Silva et al, 1998;Saad et al, 2002;Abumanssur, 2006;Blain & Brunini, 2007;Almeida et al, 2009;Cavalcante Junior et al, 2009;Peixoto et al, 2011aPeixoto et al, , 2011bVellame et al, 2012;Assis & Sousa, 2013;Borges Júnior et al, 2013;Silva et al, 2013Silva et al, , 2014Silva et al, , 2015Assis et al, 2014;Santos et al, 2014;Souza et al, 2014).…”
Section: Introductionmentioning
confidence: 99%